Pengetahuan Keluarga Pasien Tentang Tingkat Kegawatdaruratan Berdasarkan Triase Dengan Kepuasan Keluarga Pasien Di Instalasi Gawat Darurat Rumah Sakit Umum Daerah Sumedang - Situmorang, Roganda; Khotimah, Nur Intan Hayati Husnul; Aisyi, Raida Rihadatul (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: This study aims to analyze the relationship between the patient's family knowledge about emergency levels based on triage with the satisfaction of the patient's family in the Emergency Department of Sumedang Regional General Hospital. Methods: The research method uses correlational quantitative descriptive research using a cross sectional approach. The population is a family of 72 patients and the sampling technique uses accidental sampling. Data collection techniques use primary data by distributing questionnaires. The data were analyzed using frequency distribution calculations and the Chi-Square test Results: The results showed that the knowledge of the patient's family about the level of emergency based on triage was not good (12.5%), quite good (61.1%) and good (26.4%). Research also shows that the satisfaction of the patient's family in the Emergency Department is less satisfied (1.4%), quite satisfied (66.7%) and satisfied (31.9%). Research shows that there is a significant relationship (p-value 0.002) between the patient's family knowledge of emergency levels based on triage and the patient's family satisfaction in the Emergency Department. Conclusion: The results of this study are expected to provide information for hospitals to further improve education or strengthening information through print or digital media about emergency levels based on triage in the Emergency Department in order to provide positive support for increasing patient family satisfaction.